2012
DOI: 10.1016/j.febslet.2012.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of SPE‐39 due to tyrosine phosphorylation and ubiquitination on the function of Vps33B in the EGF‐stimulated cells

Abstract: a b s t r a c tAlthough SPE-39 is a binding protein to Vps33B that is one of the subunit in the mammalian HOPS complex, the elements of SPE-39 function remain unknown. Here, we show that tyrosine phosphorylation of SPE-39 following EGF stimulation plays a role in the stability of SPE-39 itself. Ubiquitination of the C-terminal region of SPE-39 was also elevated in response to EGF stimulation, and this process was regulated by the phosphorylation of Tyr-11 in SPE-39. However, association of Vps33B with SPE-39 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…By contrast, in LPS-stimulated macrophages Ac-LDL appears to be shunted into a different pathway that requires Vps33B for lysosomal delivery. It is important to note here that Vps33B and VIPAS39 are phosphorylated in response to LPS-mediated activation (Chen et al, 2012; Sjoelund et al, 2014) and their activity is regulated by phosphorylation (Bach et al, 2008; Ishii et al, 2012). In particular, dephosphorylation of Vps33B by PtpA of Mycobacteria leads to inhibition of phagolysosomal fusion (Bach et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in LPS-stimulated macrophages Ac-LDL appears to be shunted into a different pathway that requires Vps33B for lysosomal delivery. It is important to note here that Vps33B and VIPAS39 are phosphorylated in response to LPS-mediated activation (Chen et al, 2012; Sjoelund et al, 2014) and their activity is regulated by phosphorylation (Bach et al, 2008; Ishii et al, 2012). In particular, dephosphorylation of Vps33B by PtpA of Mycobacteria leads to inhibition of phagolysosomal fusion (Bach et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The role of VPS33B-VIPAR complexes are suggested to involve the RAB11A-dependent apical recycling pathway and transcriptional regulation of adherent proteins such as E-cadherin, which ensures normal cellular structure with apical basolateral polarity [ 6 ]. It is noteworthy that further research has confirmed the role of epidermal growth factor (EGF) stimulation in the interactions between SPE-39—the Caenorhabditis elegans ortholog of VIPAR—and Vps33B by tyrosine phosphorylation and ubiquitination of SPE-39 [ 11 - 13 ]. Alternatively, the apical membrane protein was observed to be misrecruited to basolateral membranes and into the late endosomes and lysosomes in knockdown/knockout studies of VPS33B or VIPAR [ 14 ].…”
Section: Introductionmentioning
confidence: 99%